LEGAL HANDLING OF CHILD MARRIAGE AS A VIOLATION OF HUMAN RIGHTS (CRITICAL STUDY OF WOMEN'S RIGHTS IN GENDER EQUALITY FROM THE PERSPECTIVE OF CRIMINAL ISSUES AND CRIME ERADICATION) - Dwiprigitaningtias, Indah; Muhammad Adystia Sunggara; Yaris Adhial Fajrin; Muhammad Bagus Adi Wicaksono; Endang Mustikowati; Liza Utama (Fakultas Hukum Universitas Kristen Indonesia Paulus, 2024)
Within the framework of human rights and the effects on gender equality, this study seeks to mainly clarify the philosophical elements of child marriage. The study takes a normative legal research stance in its examination of this matter, with an emphasis on the examination of legal principles, doctrines, and norms as solutions to legal problems. Normative juridical research, sometimes called legal product research, is the methodology used in this study. According to the results of the study, there are several philosophical problems with the concept of child marriage. The practice of underage marriage is harmful on many levels and greatly hinders children's development. Child marriage must also stop if we are to reach gender equality in society, according to the report. The ideal of gender parity will remain a distant dream so long as societies practise child marriage. The reason for this is that child marriage serves to reinforce preexisting gender stereotypes and impedes societal attempts to achieve gender equality. Thus, one must take great pains to eradicate child marriage if true gender equality is to be achieved.